Penguatan Kurikulum Merdeka melalui Pelatihan Penyusunan Modul Ajar MGMP Sejarah Kabupaten Kudus - Utama, Nanda Julian; Amin, Syaiful; Lusianto, Junaidi Fery; Khotimah, Siti Khusnul; Kristanto, Nathanael Agung; Sahab, Dhoni Frizky Arya (Universitas Gajah Putih, Indonesia, 2023)
The independent curriculum, which was expected to serve as a bridge following the slowdown in the learning process during Covid-19, has instead created new problems in its implementation. This is because the application of this curriculum lacked preparation from various parties. The History Teachers' Working Group (MGMP Sejarah) in Kudus District is one of the users encountering challenges in implementing the independent curriculum. The issues faced include: understanding the implementation of the independent curriculum and its application in teaching, especially in the development of teaching modules for Phase F in history education, which is still very limited. There is a lack of teachers' strategies in implementing the independent curriculum in schools, and a shortage of activities that support the skills and understanding of partners to implement the independent curriculum. To address these problems, the service team and partners agreed to conduct training and mentoring activities for the implementation of the independent curriculum, especially in developing Phase F teaching modules for history subjects in partner schools. The method used for this activity is training. Based on the conducted activities, it was found that participants' responses, as indicated by the survey, showed that the objectives of this service activity have been achieved. The evaluation results of the training activities, including participants' enthusiasm, level of participation, and understanding of the training materials, were very high. While the overall evaluation of the service activities also showed positive responses, there are still some areas that need improvement.